AB1114 Juvenile idiopathic arthritis: Can mother mood be a determinant factor in the child illness management?. (23rd January 2014) - Officioso, A.; Griso, G.; Russo, G.; Storace, C.; Alessio, M.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) is a chronic disease that causes children to have swelling, pain, and stiffness in their joints. JIA occurs before the age of 16. In particular child's social, emotional and also cognitive development is not always in accordance with their age and peers. It isn't unusual for someone who is living with pain, fatigue and loss of function to feel overwhelmed, depressed and anxious about the future. All chronic illnesses, have wide-reaching effects that impact not only the child, but other family members as well. Families experiencing childhood chronic illness must adapt to care giving burdens, stress, and anxiety demands. Being the parent of a child with any chronic illness can be difficult. Often parents are involved in guiding their teenager into taking more control and learning how to care for his or her own disease. And this condition can trigger depression in a family member. Objectives: to investigate some psychological issues related to JIA, in particular, the relation existing between mother's depression and child's depression Methods: Participants included 30 children (M=10, F=20), aged 7, 9±3, 4 and 30 mothers, aged 41, 5±4, 9 matched for social class. The level of depression of the children was investigated by Kovac's children's depression inventory (CDI). This test provides information about the youth's scores and how they compare with the scores of the normative sample of non-clinical individuals. The psychological status of their mothers was assessed by the psychological general well-being (PGWB) covering the 6 affective states of health-related quality of life, anxiety, depressed mood, sense of positive well-being, self-control, general health, and vitality. Measures of unfunctional disability were completed. CDI results are been incorporated with other information as a direct clinical observation of the youth, and information about the youth's background, family history, and school adjustment. Results: Physical and psychological domains concerning individual's overall perception of quality of life resulted impaired in mothers of JV children. The level of depression of the child can be correlated with the mother's level of quality of life. Conclusions: Adolescents experience higher levels of depression and a lower quality of life as they realize the impact their disease will have on their life. Anxiety and stress are high also among parents as they deal with the worries related to their adolescent's growing independence and their own struggles over allowing the teenager to have that freedom to control his or her own health. Disclosure of Interest: None Declared